Control of angiogenesis and host response by modulating the cell adhesion properties of an Elastin-Like Recombinamer-based hydrogel. (August 2017) - Staubli, Sebastian Manuel; Cerino, Giulia; Gonzalez De Torre, Israel; Alonso, Matilde; Oertli, Daniel; Eckstein, Friedrich; Glatz, Katharina; Rodríguez Cabello, José Carlos; Marsano, Anna
Abstract: The control of the in vivo vascularization of engineered tissue substitutes is essential in order to obtain either a rapid induction or a complete inhibition of the process (e.g. in muscles and hyaline-cartilage, respectively). Among the several polymers available, Elastin-Like Recombinamers (ELR)-based hydrogel stands out as a promising material for tissue engineering thanks to its viscoelastic properties, non-toxicity, and non-immunogenicity. In this study, we hypothesized that varying the cell adhesion properties of ELR-hydrogels could modulate the high angiogenic potential of adipose tissue-derived stromal vascular fraction (SVF) cells, predominantly composed of endothelial/mural and mesenchymal cells. Human SVF cells, embedded in RGD-REDV-bioactivated or unmodified ELR-hydrogels, were implanted in rat subcutaneous pockets either immediately or upon 5-day-culture in perfusion-bioreactors. Perfusion-based culture enhanced the endothelial cell cord-like-organization and the release of pro-angiogenic factors in functionalized constructs. While in vivo vascularization and host cell infiltration within the bioactivated gels were highly enhanced, the two processes were strongly inhibited in non-functionalized SVF-based hydrogels up to 28 days. ELR-based hydrogels showed a great potential to determine the successful integration of engineered substitutes thanks to their capacity to finely control the angiogenic/inflammation process at the recipient site, even in presence of SVF cells.